PENGARUH KOMPETENSI APARAT PENGELOLA KEUANGAN DESA, SISTEM PENGENDALIAN INTERNAL PEMERINTAH (SPIP), DAN PARTISIPASIMASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGANDESA DI KABUPATEN INDRAGIRI HILIR - Ilham, Akbar; Ruhul, Fitrios; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine (1) Does the competence of village financial management officials affect the accountability of village financial management, (2) Does the government's internal control system affect the accountability of village financial management, (3) Does community participation affect the accountability of village financial management.This study uses a questionnaire, the questionnaire is an instrument to obtain data by providing a list of questions that will be filled by respondents who were determined as research samples. The research sample is village officials who manage village finances, using the saturated sample method. The unit of analysis in this study consists of: Village Head, Secretary, and Kaur Element. So that the total sample in this study was 99 village officials. The analytical method used in the study is structural equation modeling (SEM) and the analysis instrument used is partial least squares (PLS) software.The results showed that the difficulty of competence of village financial management apparatus, the government's internal control system, and community participation affected the accountability of village financial management.Keywords: the competence of the village financial management apparatus, the government’s internalcontrol system, community participation